An Analysis of Personification Found in John Meyer's Selected Song Lyrics - Ni Putu Puspa Wedayanti (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study is mainly aimed at finding out the personification type in figurative language and the meaning of personification found in John Meyer’s selected song lyrics. The data source are John Meyer’s selected song lyrics. To answer the first problem, this study used theory proposed by Knickerbocker and Reninger (1963) about figurative language and classified the song lyrics into one type namely personification. Meanwhile to answer the second problem the theory of meaning proposed by Leech (1981) was used. There are six song lyrics by John Meyer analyzed in this study. This study used qualitative descriptive analysis. The analysis was started by continuously listening to the selected songs by John Meyer. Afterward, the researcher read the lyrics of the selected songs, wrote down and categorized it into personification expression. Based on the analysis, the researcher found the 5 total of personification and 5 connotative meaning in John Meyer’s selected song lyrics.